Assessment of lettuces grown in urban areas for human consumption and as bioindicators of atmospheric pollution - Izquierdo-Díaz, Miguel; Hansen, Veronika; Barrio-Parra, Fernando; De Miguel, Eduardo; You, Yawen; Magid, Jakob (Ecotoxicology and environmental safety, 2023)
This study proposes using the network of urban gardens to grow vegetables and to monitor air quality, and it also evaluates whether food grown on a clean substrate in an urban environment is safe for consumption. For this purpose, lettuces were exposed to different degrees of air pollution in five locations in the city of Copenhagen, plus a reference site. Six specimens were placed at each site and, after the exposure period, half of each sample was washed. Subsamples were then digested by a total extraction method and a bioaccessible extraction method, and the concentration of 23 elements subsequently measured by ICP-MS. The results showed that exposed samples in areas of higher atmospheric pollution accumulated a larger amount of trace elements associated with typical urban sources. They also highlighted the importance of washing food to remove particles that adhere to their surface. However, bioaccessibility testing demonstrated the importance of including bioaccessibility in risk analyses and how this factor varies depending on the type of matrix. In this case, bioaccessibility was higher for plant tissue than for particulate matter. Lastly, metal concentrations in lettuce were compared with legal values and an analysis of daily intake showed that the levels in Copenhagen were within limits for the protection of human health. [Display omitted] •Urban gardens can be used as sites for biomonitoring of atmospheric pollution levels.•Many urban-related pollutants are primarily associated with PM deposited on leaves.•It is advisable to grow food in low-traffic areas and wash it thoroughly.•Trace element bioaccessibility values vary depending on the type of solid matrix.•Lettuce grown in an urban area on clean substrate is within health safety limits.